Non-targeted metabolomics reveals myocardial metabolic alterations in epileptic rats - Yue Hu; Yusen Wang; Qinghong Mao; Shisheng Zhu; Li Zhang (PLoS ONE, 2026)
Sudden unexpected death in epilepsy (SUDEP) is closely associated with cardiovascular dysfunction, yet its mechanisms remain unclear. Emerging evidence suggests that epilepsy-induced cardiac dysfunction may play a central role. Metabolomics provides a powerful approach to comprehensively characterize these metabolic alterations, enabling biomarker discovery and mechanistic insight into epilepsy-related cardiac injury. Here, we used UHPLC-OE-MS-based non-targeted metabolomics to systematically characterize myocardial metabolism in epileptic rats, aiming to identify epilepsy-related myocardial metabolic biomarkers, explore their biological significance, and elucidate mechanisms underlying epilepsy-induced cardiac dysfunction. In this study, we employed UHPLC-OE-MS-based non-targeted metabolomics to systematically profile myocardial metabolic changes in a pentylenetetrazol (PTZ)-induced epileptic rat model. Myocardial tissues from epileptic and control rats were analyzed using multivariate statistical methods, including principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA), to identify significantly altered metabolites. KEGG pathway enrichment analysis was performed to elucidate the biological relevance of these metabolic disturbances. Histopathological examination revealed marked neuronal disorganization and myocardial injury in epileptic rats, characterized by cardiomyocyte swelling, nuclear pyknosis, and interstitial edema. Metabolomic analysis identified 127 differential metabolites, primarily involved in amino acid metabolism, glycerophospholipid metabolism, and energy metabolism. Notably, L-glutamine, L-phenylalanine, L-alanine, and β-alanine were significantly reduced, potentially contributing to glutamate/GABA imbalance, excitotoxicity, and oxidative stress. Additionally, dysregulated glycerophospholipids (e.g., LysoPC, PC, and PE) and altered pantothenate and CoA biosynthesis indicated compromised membrane integrity and impaired energy metabolism in epileptic myocardium. ROC analysis demonstrated excellent diagnostic performance of key metabolites (AUC > 0.98), highlighting their potential as biomarkers for epilepsy-related cardiac dysfunction.